2017
DOI: 10.1590/1981-22562017020.160088
|View full text |Cite
|
Sign up to set email alerts
|

The perspective of caregivers of people with Parkinson's: an integrative review

Abstract: Objective: to analyze scientific production regarding the process of caring for persons with Parkinson's Disease (PD) from the perspective of the caregiver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…They also corroborate that the family and caregiver can break paradigms about PD and fall prevention, and work with the elderly in their entirety. Thus, care becomes light and dynamic, reducing the emotional, social and physical overload that falls on them (32)(33)(34) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also corroborate that the family and caregiver can break paradigms about PD and fall prevention, and work with the elderly in their entirety. Thus, care becomes light and dynamic, reducing the emotional, social and physical overload that falls on them (32)(33)(34) .…”
Section: Discussionmentioning
confidence: 99%
“…This goal addresses the needs of the elderly with PD, which, due to the reduction of the speed of muscular contraction, causes the reduction of the protection reflex and of the response to the stretching of the muscle, resulting in the loss or reduction of the balance. These factors, added to the biological changes, increase the disposition for falls, that can bring countless repercussions to the life of the elderly from fractures, loss of social life, hospitalizations and even death (15)(16)(17) .…”
Section: Introductionmentioning
confidence: 99%
“…Accepting the outcome of the diagnosis and remaining calm though less frequent may help individuals make right decisions as to what to do next. In accordance with this claim, Ferreira et al [10], in their integrative review, have identified learning to act calmly, positive thinking, and more patience as key ingredients of positive aspects for caregivers of PD patients.…”
Section: Discussionmentioning
confidence: 86%
“…However, how one reacts to the outcome of PD diagnosis is likely to affect the subsequent actions she/he would take. Negative overreactions as well as unresponsiveness are likely to lead to negative aspects in the caregivers and compromise the cares they are supposed to provide to the patient [10]. Accepting the outcome of the diagnosis and remaining calm though less frequent may help individuals make right decisions as to what to do next.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation